Prevalence of pre-eclampsia and eclampsia risk factors among pregnant women, 2011-2013 - F, Kahnamouei-aghdam; F, Amani; S, Hamidimoghaddam (International Journal of Advances in Medicine, 2017)
Background: Pre-eclampsia is a common problem during pregnancy which complicated 5 to 10 % of total pregnancies and 20 % of first pregnancies. Mothers with pre-eclampsia are at higher risk of maternal and fetal complications. The aim of this study was to estimate the prevalence of pre-eclampsia and eclampsia risk factors among pregnant women. Methods: In this cross-sectional study in 2011-2013, 592 Pre-eclampsia and eclampsia mothers have been studied. Information gathered by a checklist include information about risk factors of PE&E such as age up 30,family history, abortion, HTN, thrombophilia, diabetes before pregnancy, parity, renal failure, infertility and twin birth from archived files in hospital. Gathered data analyzed by statistical methods in SPSS-19. The level of significance was p<0.05. Results: From all files 18 cases (3%) were eclampsia and rest of them were Pre-eclampsia (55.2% with mild and 41.7% with sever PE). There was no significant relation between PE and E incidence with variables such as history PE, age, family history, twin birth, abortion, thrombophilia, infertility, renal failure and Urinary symptoms. Conclusions: Results showed that in Ardabil province, the prevalence of PE was almost similar with other studies. Various factors could be effective in PE and E incidence which between these factors we can point to chronic HTN in mother, diabetic before pregnancy and gravity in this study.